Hubungan Bauran Pemasaran dan Faktor Psikologis dengan Proses Pengambilan Keputusan Pasien dalam Pemanfaatan Rawat Jalan (Relation of Marketing Mix and Psychological Factors with Patient's Decision-Making Process in Outpatient Services Utilization) - Fathur Rachman Hakim; Nuryadi Nuryadi; Christyana Sandra (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Based on the results of preliminary study have been found decrease in the number ofoutpatient visits in Balung Regional Hospital every years at 2010-2013 with an averageby 5.41%. Considering that indicators of outpatient utilization rate based on the numberof visits per day (within a period of 1 year), and utilization rate of the patient depends onthe decision to use it, therefore concluded that patient's decision to utilize outpatientservices in Balung Regional Hospital were less good. The purpose of this research wasanalyze the relation of marketing mix and psychological factors with patient's decisionmaking process in outpatient services utilization in Balung Regional Hospital, Jember.This research was an analytical design by cross sectional, with number of sampleswere136 of public patients who use outpatient services in 2014. The data were analyzedstatistically by using association Somer's D test. The results showed relationshipbetween place, product, price, promotion, people and process with patient's decisionmaking process. But there was no relationship between physical evidence with patient'sdecision making process. Furthermore, there was relationship between perception,motivation, and attitude with patient's decision making process in outpatient services.Keywords: Marketing Mix, Psychological Factor, Decision Making Process